ANALISIS PENGARUH NILAI TUKAR TERHADAP HARGA SAHAM LQ45 DENGAN METODE EGARCH (2012-2015) - Natalia Annastasia; Yudith Dyah Hapsari (Prosiding Working Papers Series In Management, 2018)
This study aims to investigate the effect of exchange rate and previous period index price of LQ45 towards LQ45 index. This study is done by utilizing ARCH/GARCH model with the specification EGARCH using the daily historical data during the 2010-2015 periods. The result of this study shows indicates that exchange rate and the index price of previous period significantly affect LQ45 index. Furthermore, there is only one company listed in LQ45, PT. Jasa Marga which transactions and financing did not using any foreign currency.Keywords: EGARCH, Exchange Rate, LQ45.